Proteomic Signatures and Blood Adenosine Triphosphate Levels as Markers of Empagliflozin Efficacy in Type 2 Diabetes Mellitus and Heart Failure - Omurzakova, Uulkan; Breidert, Matthias; Donner, Markus; Toktogulova, Nurgul; Moldobaeva, Maria; Quartier, Angélique; Eftekhari, Pierre (Hormone and Metabolic Research, 2025)
Empagliflozin, a sodium-glucose cotransporter 2 inhibitor, is approved for the treatment of type 2 diabetes mellitus and heart failure. Its known ability to enhance mitochondrial adenosine triphosphate production and improve cardiac function led us to investigate whether blood adenosine triphosphate levels could serve as a predictive biomarker for treatment response. This prospective study included 120 patients from Kyrgyzstan: 49 with type 2 diabetes mellitus, 43 with heart failure, and 28 with both type 2 diabetes mellitus and heart failure. The mean age of the study population was 63.9±7.1 years, with no significant age difference between groups. Patients received oral empagliflozin at a dose of either 10 or 25 mg daily for 12 weeks. Adenosine triphosphate activity was measured in erythrocytes from whole blood samples before and after treatment. In vitro assays were also performed, incubating patient blood samples with empagliflozin at concentrations of 0.1, 1, and 10 µM. In patients with type 2 diabetes mellitus, empagliflozin significantly reduced body mass index (p=0.001), though HbA1c levels remained unchanged. Among heart failure patients, treatment resulted in a significant increase in left ventricular ejection fraction (p=0.028) and a decrease in B-type natriuretic peptide levels (p=0.01). Blood adenosine triphosphate concentrations increased significantly following empagliflozin treatment in both type 2 diabetes mellitus and heart failure groups. Proteomic analysis identified 12 differentially expressed proteins—ADIPOQ, ARG1, CST3, CPPED1, GSTO1, FN1, ITIH4, LCN2, LCP1, MIF, PCMT1, and SERPINA3—that are functionally linked to type 2 diabetes mellitus and/or heart failure pathophysiology. Our data suggest that blood adenosine triphosphate activity may serve as a potential biomarker for clinical response to empagliflozin in patients with type 2 diabetes mellitus and heart failure. Further studies are warranted to validate these exploratory findings and to evaluate the sensitivity, specificity, and predictive value of blood adenosine triphosphate as a biomarker in these populations.
Keywords: diabetes mellitus type 2; cardiometabolic disease; heart failure; empagliflozin; proteomics